Menumbuhkan Jiwa Kewirausahaan Melalui Koperasi Mahasiswa - Nirmayani, L. Heny; Suastika, I Nengah (Universitas Pendidikan Ganesha, 2023)
The entrepreneurial spirit must be cultivated from an early age. Through art and skills in entrepreneurship, they are able to create business opportunities for themselves and society. Creating creative and innovative business fields is able to grow the wheels of the family, community and state economy. Entrepreneurship learning in theory and practice can be started in a school environment. Through the application of theory towards real practice, the entrepreneurial spirit is increasingly active, developing and even advancing. In the college environment, the application of an entrepreneurial spirit is realized through student cooperatives. Through student cooperatives, it is hoped that qualified entrepreneurial spirits will grow. Good and professional management and management will be able to develop a healthy student cooperative.